If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2 + n) = 0 (2 * 5 + n * 5) = 0 (10 + 5n) = 0 Solving 10 + 5n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 5n = 0 + -10 Combine like terms: 10 + -10 = 0 0 + 5n = 0 + -10 5n = 0 + -10 Combine like terms: 0 + -10 = -10 5n = -10 Divide each side by '5'. n = -2 Simplifying n = -2
| 30=12b | | 5r+25=31+5r | | 2g-13h+15=x | | (5x-38)=(3x-4) | | 4(x-1)+6=2x-5(1+x) | | -3x+3+7x=-13 | | 2/3x-5=20 | | 11y-1=5.75 | | (1/3)(27) | | 2.49(n+1.24)=11.17 | | 10y+10+5x=180 | | -2-2/3=12 | | 4.23-7.2x=3.6x-9 | | -2(3x+5)+4x=4 | | -12+4x=7x+17 | | -100(m-80)=4 | | (2x-5)+(4x+6)= | | 9x+44=9x-44 | | 6*-4+24= | | 6x+12y=288 | | 4=5x+3-5x | | -12790+185t=0 | | 82=2x-6 | | 4=5x+3+5x | | 2.5-8(1-5a)=-20.5 | | 4-6y=13 | | 3y-3x=-6 | | -8(3f+9)=18-5f | | -6s-5-2.5s=18.5 | | 8y+17=137 | | X-4.2=8.02 | | 27.5=-4+3(b+6.5) |